Clinical Predictors of Survival and Functional Outcome of Stroke Patients Admitted to Critical Care*. Issue 7 (July 2018) - van Valburg, Mariëlle K.; Arbous, M. Sesmu; Georgieva, Milena; Brealey, David A.; Singer, Mervyn; Geerts, Bart F.
Abstract : Objectives: To determine the predictive value of commonly used clinical variables upon ICU admission for long-term all-cause mortality and functional outcome of adult stroke patients admitted to the ICU. Design: Retrospective observational cohort study. Setting: General and neurosurgical ICUs of the University College London Hospitals in North Central London. Patients: All adult ICU patients with a clinical diagnosis of acute stroke admitted between February 2010 and May 2012. Interventions: None. Measurements and Main Results: Demographic and clinical data concerning the first 24 hours after ICU admission were obtained. Patients were followed until February 2016 to assess long-term survival. Functional outcome was determined using the modified Rankin Scale. We evaluated 131 critically ill stroke patients, with a median (interquartile range) age of 70 years (55–78 yr). One-year mortality rate was 52.7%. Surviving patients were followed up over a median (interquartile range) period of 4.3 years (4.0–4.8 yr). The multivariable model that best predicted long-term all-cause mortality indicated that mortality of critically ill stroke patients was predicted by high Acute Physiology and Chronic Health Evaluation II score, impaired consciousness (Glasgow Coma Scale score ⩽ 8) as reason for ICU admission, low Glasgow Coma Scale sum score after 24 hours, and absence of brainstem reflexes. Long-term independent functional status occurred in 30.9% of surviving patients and was predicted by low Acute Physiology and Chronic Health Evaluation II score, high Glasgow Coma Scale sum score at ICU admission, and absence of mass effect on CT scan. Conclusions: Mortality in critically ill stroke patients is high and occurs most often shortly after the event. Less than one in three surviving patients is able to function independently after 1 year. This study has identified several clinical variables that predict long-term all-cause mortality and functional outcome among critically ill stroke patients and found that mainly acute physiologic disturbance and absolute values of neurologic clinical assessment are predictive. Abstract : Supplemental Digital Content is available in the text.